2017
DOI: 10.1080/01596306.2017.1316705
|View full text |Cite
|
Sign up to set email alerts
|

Mapping discourses on mosque education in the Netherlands: a content analysis of the Dutch press, 2010–2016

Abstract: This article provides an overview of the discourses on Dutch mosque education. Based on a review of the scholarly debates on mosque education in West, we conducted a qualitative content analysis of newspaper articles containing references to mosque education between 2010 and 2016 (N = 45). The data are sampled from the five largest Dutch newspapers. Most of the themes emerging from the literature are also reflected in the discourses on mosque education in the press. In line with other media analysis on represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Using corporal punishment as a discipline measure is one of the most notorious ways mosques appeared in the Dutch media in the past decade (Sözeri, Altinyelken, and Volman 2017). Several educators as well as parents mentioned how as children they had either experienced or witnessed corporal punishment in mosques in Turkey or in the Netherlands.…”
Section: Classroom Management and Discipline Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using corporal punishment as a discipline measure is one of the most notorious ways mosques appeared in the Dutch media in the past decade (Sözeri, Altinyelken, and Volman 2017). Several educators as well as parents mentioned how as children they had either experienced or witnessed corporal punishment in mosques in Turkey or in the Netherlands.…”
Section: Classroom Management and Discipline Strategiesmentioning
confidence: 99%
“…In recent years, mosque education has received unprecedented scrutiny from policymakers and wider public whose perceptions are largely shaped by the media in a decidedly critical way (Sözeri, Altinyelken, and Volman 2017). It is often linked to growing concerns in Europe that Muslim immigrants do not share the core values of liberal democratic societies, and mosques might reproduce conservative dispositions.…”
mentioning
confidence: 99%
“…The data revealed that prior to the events of September 11, the coverage mostly focussed on the personal experiences of Muslims who were devout, yet after the attacks, the attention switched to the relationship between religious fanaticism and integration. On the other hand, an investigation into the articles that were published in the widely read newspaper known as De Algemeene Dagblad (AD) and that were associated with Islam (Sözeri et al, 2017). Their findings indicate that there has been a significant increase in the negative framing of domestic Islam since the assassination of the Dutch filmmaker Theo van Gogh in 2004, which was carried out by a radical of Dutch-Moroccan origin.…”
Section: Western Media's Representation Of Muslims and Islammentioning
confidence: 99%
“…The data revealed that prior to the events of September 11, the coverage mostly focussed on the personal experiences of Muslims who were devout, yet after the attacks, the attention switched to the relationship between religious fanaticism and integration. On the other hand, an investigation into the articles that were published in the widely read newspaper known as De Algemeene Dagblad (AD) and that were associated with Islam (Sözeri et al, 2017). Their findings indicate that there has been a significant increase in the negative framing of domestic Islam since the assassination of the Dutch filmmaker Theo van Gogh in 2004, which was carried out by a radical of Dutch-Moroccan origin.…”
Section: Western Media's Representation Of Muslims and Islammentioning
confidence: 99%